PENGEMBANGAN MULTIMEDIA INTERAKTIF TERINTEGRASI PENDIDIKAN KARAKTER PADA MATERI JARINGAN TUMBUHAN DI KELAS XI SMA NEGERI 13 MEDAN T.P 2021/2022 - Monica Rosephine Afriyanti Sitanggang; Hudson Sidabutar (BEST Journal (Biology Education, Sains and Technology), 2022)
This study aims to determine: (1) the feasibility of integrated interactive multimedia learning materials for character education for class XI MIA SMA Negeri 13 Medan T.P 2021/2022; (2) The feasibility of integrated interactive multimedia learning media for character education for class XI MIA SMA Negeri 13 Medan T.P 2021/2022; (3) Biology teacher's response to interactive multimedia integrated character education on plant tissue material in class XI MIA SMA Negeri 13 Medan; (4) Student responses to interactive multimedia integrated character education in plant tissue material in class XI MIA SMA Negeri 13 Medan T.P 2021/2022; (5) the effectiveness of the use of Integrated Interactive Multimedia Character Education on plant tissue material developed to improve learning outcomes; (6) implementation of character values applied to interactive multimedia integrated character education developed in the learning process. This type of research is development research with a modified 4-D product development model as needed. The test subjects consisted of material experts, media experts, biology teacher assessments, responses from class XI MIA 7 students at SMA Negeri 13 Medan, 6 students from class XI MIA 7 at SMA Negeri 13 Medan in the small group test, and 30 students from class XI MIA 7 at SMA Negeri 13 Medan in a limited group trial. Product development quality data were collected by questionnaire. Data were analyzed by quantitative and qualitative descriptive techniques. The results showed that: (1) Material expert validation was in the "Very Eligible" criteria (88.32%); (2) Validation of media experts is in the criteria of "Very Eligible" (93.6%); (3) The assessment of biology teachers is in the "very appropriate" criteria (92.6%); (4) The small group trial was met with the criteria of "Very Good" (89.16%); (6) In the limited group trial, the criteria were "Very Good" (92.5 %).